Dissipation and Effect of Processing of λ-Cyhalothrin Residues in Brinjal - Reddy, C. Narendra; Reddy, D. Jagdishwar; Rahman, S. M. A. S. (International Journal of Bio-resource and Stress Management, 2012)
The experiment was conducted during kharif, 2009 at College of Agriculture, ANGRAU, Rajendranagar, Hyderabad, India in a randomized block design with four replications. The dissipation pattern of λ-Cyhalothrin revealed that initial deposit of λ-Cyhalothrin (1.36 mg kg-1) was dissipated to below detectable residues at 10 days after third spray when λ-Cyhalothrin was sprayed @ 15 g a.i. ha-1. While, in case of double dose, the initial deposit (1.84 mg kg-1) was dissipated to below detectable level at 15 days after third spray. The waiting period for safe harvest of brinjal fruits after three sprays of λ-Cyhalothrin @ 15 and 30 g a.i. ha were 5.05 and 7.67 days, respectively. The washing of brinjal fruits collected on 5th day after third spray with tap water for 2 minutes removed residues of λ-Cyhalothrin to the extent of 33.34 to 36.11% in both the treatments. The washing of brinjal fruits with 2% salt water for 2 minutes removed residues of λ-Cyhalothrin to the extent of 62.96 to 63.89% in both the treatments on 5th day after third spray.